Risk Management and Bank Profitability: Moderating Effects on Lending and Credit Risk in Indonesia - Dwi Nita Aryani; Helmi Hasan Assegaf (International Journal of Applied Business and International Management, 2026)
Banks face credit and liquidity risks that affect profitability and financial stability. This study examines the effects of the Loan-to-Deposit Ratio (LDR) and Non-Performing Loans (NPL) on Return on Assets (ROA) in Indonesian banking, as well as the moderating role of risk management and the mediating role of NPL in the relationship between LDR and ROA. This study employed a quantitative approach using panel data from 30 commercial banks, resulting in 300 bank-year observations. The data were analyzed using Moderated Regression Analysis (MRA) with SPSS. The findings show that LDR positively affects ROA (? = 0.020; p = 0.035), while NPL negatively affects ROA (? = ?0.340; p = 0.009). Risk management does not directly affect ROA (? = 0.375; p = 0.486), but it significantly moderates the relationship between LDR and NPL (? = 0.007, p = 0.039) and reduces the negative effect of NPL on ROA (? = ?0.098; p = 0.024). NPL does not mediate the relationship between LDR and ROA. This study contributes to the development of agency theory and risk management. The research implication is to raise awareness of the importance of risk management for banks, helping them reduce risks and increase profits.